Accuracy of defining characteristics of the nursing diagnosis Ineffective Role Performance - Rhayza Rhavênia Rodrigues Jordão; Bárbara Maranhão Calábria Cavalcanti; Denise Cibelle Rodrigues Marques; Jaqueline Galdino Albuquerque Perrelli; Suzana de Oliveira Mangueira; Fernanda Jorge Guimarães; Iracema da Silva Frazão (Universidade Federal de Goias, 2017)
The study objective was to verify the accuracy of the defining characteristics of the nursing diagnosis Ineffective Role Performance in pregnant women. This is an accuracy diagnosis study conducted with 58 women attended in Family Health Units (FHU). We used a tracking scale for Postpartum Depression to identify the defining characteristics of the referred diagnosis. We calculated sensitivity, specificity measures, and their respective confidence intervals. The Ineffective Role Performance was present in 50.0% of participants. The defining characteristics Inadequate adaptation to change, Insufficient self-management, and Alteration in role perception simultaneously presented, significant sensitivity and specificity, in statistical terms. Therefore, such clinical indexes were more accurate to verify the nursing diagnosis Ineffective Role Performance in pregnant women.